Characterization of lime plaster of Ipoh Royal Club for conservation purpose / Farah Reeza Abdul Razak and Siti Norlizaiha Harun - Abdul Razak, Farah Reeza; Harun, Siti Norlizaiha (2015)
This study addresses the defects and performance of lime mortar and plaster due to dampness which is one of the most severe occurrences that leads heritage building to decay and deteriorate. Acting as main component of building's historic fabric, lime mortar and plaster are significantly affected by environmental factors and thus demand further proper conservation and repair works. The lack of understanding on the evolution of the material characteristics and wrong decision making on the new composition of lime has further resulted in the recurrence of decay and deterioration of the material. The purpose of this study intends to investigate and identify the lead source of dampness in the walls of this heritage building in Ipoh. The detail study sought to determine and analyse scientifically the original mortar and plaster characteristics in terms of their moisture content, strength and composition which is affected by dampness. The knowledge of the decay progressions and its contributing elements with the studied characteristics of the material will allow a better understanding on the usage of this material as well as proper training to interpret clues on techniques in order to succeed in future conservation works.